Genomewide Association Study of Alcohol Dependence Identifies Risk Loci Altering Ethanol‐Response Behaviors in Model Organisms. (30th March 2017) - Adkins, Amy E.; Hack, Laura M.; Bigdeli, Tim B.; Williamson, Vernell S.; McMichael, G. Omari; Mamdani, Mohammed; Edwards, Alexis C.; Aliev, Fazil; Chan, Robin F.; Bhandari, Poonam; Raabe, Richard C.; Alaimo, Joseph T.; et al.
Abstract : Background: Alcohol dependence (AD) shows evidence for genetic liability, but genes influencing risk remain largely unidentified. Methods: We conducted a genomewide association study in 706 related AD cases and 1, 748 unscreened population controls from Ireland. We sought replication in 15, 496 samples of European descent. We used model organisms (MOs) to assess the role of orthologous genes in ethanol (EtOH)‐response behaviors. We tested 1 primate‐specific gene for expression differences in case/control postmortem brain tissue. Results: We detected significant association in COL6A3 and suggestive association in 2 previously implicated loci, KLF12 and RYR3 . None of these signals are significant in replication. A suggestive signal in the long noncoding RNA LOC339975 is significant in case:control meta‐analysis, but not in a population sample. Knockdown of a COL6A3 ortholog in Caenorhabditis elegans reduced EtOH sensitivity. Col6a3 expression correlated with handling‐induced convulsions in mice. Loss of function of the KLF12 ortholog in C. elegans impaired development of acute functional tolerance (AFT). Klf12 expression correlated with locomotor activation following EtOH injection in mice. Loss of function of the RYR3 ortholog reduced EtOH sensitivity in C. elegans and rapid tolerance in Drosophila . The ryanodine receptor antagonist dantrolene reduced motivation to self‐administer EtOH in rats. Expression of LOC339975 does not differ between cases and controls but is reduced in carriers of the associated rs11726136 allele in nucleus accumbens (NAc). Conclusions: We detect association between AD and COL6A3, KLF12, RYR3, and LOC339975 . Despite nonreplication of COL6A3, KLF12, and RYR3 signals, orthologs of these genes influence behavioral response to EtOH in MOs, suggesting potential involvement in human EtOH response and AD liability. The associated LOC339975 allele may influence gene expression in human NAc. Although the functions of long noncoding RNAs are poorly understood, there is mounting evidence implicating these genes in multiple brain functions and disorders. Abstract : A GWAS of alcohol dependence identified signals in the brain‐expressed extracellular matrix protein collagen 6A3 ( COL6A3 ) gene and the previously implicated Krueppel‐like factor 12 ( KLF12 ) and ryanodine receptor 3 ( RYR3 ) genes. Expression of COL6A3 in mouse brain is strongly correlated with handling‐induced convulsions (top inset). Knockout of the C. elegans KLF12 ortholog, Klf‐3, blocks development of acute functional tolerance (middle inset). Transheterozygous or homozygous transposon insertion in the Drosophila RYR3 ortholog, Ryr, significantly reduces the development of rapid tolerance.